The Volcanoes of Indonesia And Natural Disaster Reduction - Herman Th. Verstappen (Indonesian Journal of Geography, 1994)
Indonesian volcanism is related to the subduction (genie zones of the Lido-Australian and the Pacific-Philippine plates at the contact with the Asian plate. Rows of volcanoes perpendicular to the plate movement point to steepening of the subduction zone. with time. Strafo volcanoes and also ignimbrite plateaus associated with socalled "volcano-tectonic" depressions Of deep-seated faiths are major features. •Fluvio-volcanic flows and slopes arc common due to the humid tropical climate. Large volcanic landslides and debris flows causing rupture of crater or caldera rims and the collapse of slopes also arc important volcanic geomorphological features.The role of geomorphological survey and the use of aerospace technology in volcanic hazard zoning is emphasized